Trust and Character Development (Life Lessons from Prophet Ibrahim As) - Harmaini, Harmaini; Jannah, Putri Miftahul; Salmiyati, Salmiyati; Tahir, Kartini Radjabulan (International Journal of Islamic Educational Psychology, 2022)
Trusts can change or shape someone because they are the most vital part of personality and character development. Muslims have plenty of examples to choose from, and the author chose Prophet Ibrahim in this article. He is a pious individual whom Siti Hajar and Prophet Ismail trusted. Characters are distinctive values for mental, morals or personality due to internalizing various beliefs that become a perspective, way of thinking, and behavior. This paper aims to examine the effect of trust in someone on the formation of self-character. The source of the study was the story of the Prophet Ibrahim, Siti Hajar and Prophet Ismail, which lies in the Qur'an and many journals written by experts and scholars. The results proved that trust could grow characteristics such as sincerity, patience and optimism. Trusts also created the driving force of desire in oneself to become likable, loved and respected person by Prophet Ibrahim and Allah SWT. The main lesson taken from Prophet Ibrahim was how positive characters were formed. He acted as desired, and finally, a change occurred because of acceptance.